Urea oxidation in a paper-based microfluidic fuel cell using Escherichia coli anode electrode (2018)
ABSTRACT: Abstract. This paper presents the use of Escherichia coli as an anode in a paper-based microfluidic urea fuel cell (P-based μUFC). For the construction of this P-based μUFC, a saline solution with E. coli bacteria was deposited on carbon cloth and used as an anode for urea oxidation, furthermore, a piece of Toray® carbon paper was impregnated with Pt/C and used as an cathode to reduce the oxygen present in the air. The P-based μUFC proved with a urea solution of 0.33 M, showed an open-circuit voltage of 0.83 V, a maximum current density of 3.253 mA cm-2 and a maximum power density of 0.608 mW cm-2, these values were similar to report when human urine was used as fuel. The microfluidic fuel cell developed was evaluated for 20 consecutive days at room temperature in order to observe the lifetime of the bacteria with respect to the power generated. This work represents an advance in the possible use of physiological fluids such as urine to generate electrical energy in non-implantable medical devices.